Os Colegas, Angélica e O Sofá estampado: Lygia Bojunga e a reconstrução da fábula - Silva, Elisa Cristina da (2010)
Lygia Bojunga s work is recognized in Brazil and internationally, among other aspects, by the special treatment it conveys to the themes and language. Her texts establish a dialogue not only with children or young people, but also with the contemporary men by dealing with questions such as identity, friendship, discoveries, life, death, etc. In this research we analyse three books by Bojunga: Os Colegas (1972), Angélica (1975) and O sofá estampado (1980), which, in our opinion, form a trilogy of fables, once Lygia Bojunga s aesthetic project reveals elements which bring about mechanisms of recreation of the fable. The corpus also presents itself as highly significant, because its narratives act aesthetically as a kind of answer to a natural necessity of men. This corpus presents fast narratives, with a high degree of a stage acting suggestion, which rekindles the fable by casting a new light on it due to an updating process. Based on the literary aspects of the corpus and on fable s main features we intend to demonstrate by which compositional resources and with which aesthetic effects the corpus rescues and rewords the fable in present days. Considering that there are at least three invariable elements on the basis of all fables analogy, moral and orality our analysis will be organized around the relations which are established among these elements and the following categories: narrator, characters and reader, having the works by Maria Celeste Dezotti, Alceu Dias Lima and Susan Suleiman as a basis. Being the fable a narrative based on discourse, we tried to show the aspects of voice and orality as elements of a theatrical scene and innovation of the narrative. This analysis is based on the concepts of voice and orality and some of its aspects, such as dialogism and performance, in theories by Paul Zumthor and Mikhail Bakhtin